War, Status Quo, and Peace in the South Caucasus: A Power Transition Perspective. (2nd October 2017) - Güneylioğlu, Murat
Abstract : The regional wars in the Caucasus were frozen by the Russia's initiatives in the early 1990s. Yet, given the developments in the last twenty years and the widespread dissatisfaction among the region's people, one can argue that a just, equal, and stable peace has never been established in the region. Power transition theory puts forward a substantial perspective to analyze the regional peace in the Caucasus. The theory defines an international hierarchical order that can be symbolized as a power pyramid; peace is guaranteed when the dominant power preserves its preponderance against possible challengers dissatisfied with the status quo. The multiple hierarchy model applies this argument to regional subsystems, and defines regional hierarchies that function similarly to the international one, though they are open to external interventions. This article analyzes the status quo, peace and war in the South Caucasus from a power transition perspective. Three periods are defined: The establishment of the status quo (1991-1994), external involvement and regional competition period (1994-2008) and the aftermath of the Georgia war. Lastly future prospects will be discussed regarding Azerbaijan's growing power against Armenia and the likelihood of renewed conflicts based on dissatisfaction with the status quo.